Reversible DNA–Protein Cross‐Linking at Epigenetic DNA Marks. (6th October 2017) - Ji, Shaofei; Shao, Hongzhao; Han, Qiyuan; Seiler, Christopher L.; Tretyakova, Natalia Y.
Abstract: 5‐Formylcytosine (5fC) is an endogenous DNA modification frequently found within regulatory elements of mammalian genes. Although 5fC is an oxidation product of 5‐methylcytosine (5mC), the two epigenetic marks show distinct genome‐wide distributions and protein affinities, suggesting that they perform different functions in epigenetic signaling. A unique feature of 5fC is the presence of a potentially reactive aldehyde group in its structure. Herein, we show that 5fC bases in DNA readily form Schiff‐base conjugates with Lys side chains of nuclear proteins in vitro and in vivo. These covalent protein–DNA complexes are reversible ( t 1/2 =1.8 h), suggesting that they contribute to transcriptional regulation and chromatin remodeling. On the other hand, 5fC‐mediated DNA–protein cross‐links, if present at replication forks or actively transcribed regions, may interfere with DNA replication and transcription.